MaaS Implementation in Bandung City: Big Data Collection, Integration, and Utilization - Yogatama, Alexander Kresna; Sutapa, Jolang Sasongko; Putriani, Okkie; Mahardhika, Sakti Prajna (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2022)
The results of the Eden Strategy Institute 2021 study show that Bandung City is ranked 28th in the world's Top 50 Smart City Government Rankings. However, from the results of the Asian Development Outlook 2019 study, Bandung City is ranked as the most congested city in Indonesia and 14th in Asia. Solutions to problems are offered in the form of Mobility as a Service (MaaS), an integrated system of transportation services, digitization, and the use of big data. The realization of MaaS requires contributions from all parties. The synergy between the government, academia, stakeholders, the media, and the public is called Pentahelix. The research stage includes the collection of primary data and secondary data by conducting a literature review. Then conduct a graphical analysis of multivariate data on Pentahelix with three assessments, namely performance, competence, and involvement. Next, modeling and loading were carried out for a pilot simulation of The Bandung City area in the eastern region using macro or meso-level traffic simulation software, namely PTV Visum 2022 (Student). After comparing with real-time analysis from the Google Maps application, comprehensive results were obtained with real conditions. As a means of controlling public transportation services, an Electronic Device Capture (EDC) hardware digital system is needed that is integrated between modes through software and artificial intelligence. The final stage of this study was carried out a risk analysis matrix for the implementation of MaaS for the city of Bandung with moderate risk results. MaaS is not a new idea, but it is a good solution to overcome congestion and change Bandung's transportation concept.